Chronic prostatitis and male infertility - Lev E. Belyi (LLC "MEDIAFORMAT", 2023)
One of the factors that can lead to the development of male infertility is an infection of the genitourinary tract. An infectious and inflammatory process affecting the male reproductive system can cause various disorders of reproductive function: a disorder of gametogenesis in the testicles, disorders of sperm maturation in the epididymis, and passage of sperm along the vas deferens, as well as a decrease in some parameters of the ejaculate due to inflammatory dysfunction of the male accessory glands. Prostatitis is one of the most common urological diseases in young men. Prostatitis accounts for 25% of all requests for medical help to a urologist, and from 2 to 10% of men suffer from prostatitis symptoms. The disease is polyethological, and infection, immunological reactions, urethro-prostatic reflux of urine, psychoemotional stress are mentioned as the main causes of its development today. It is obvious that a pathological process with complex pathogenetic mechanisms affecting the prostate gland can have a negative impact on male fertility. This review examines the key mechanisms of the development of male infertility in chronic prostatitis.